Combinatietherapie bij reumatoide artritis : prioriteiten voor toekomstig onderzoek - Loo, Mirjam van het.; Beusekom, I. van (Ineke); Bots, P. W. G. (Pieter W. G.); Allaart, Renee; MacLean, Catherine H.; Breedveld, F. C.; Kahan, James P.; RAND Europe; Rand Corporation; College voor Ziekenhuisvoorzieningen (Netherlands) (Santa Monica, CA : RAND, 2001)
It is not possible to conduct randomized clinical trials (RCTs) on all the many new health care options that arise. Screening of these options is necessary, based upon reducing uncertainty in the clinical community about their appropriateness. The RAND/UCLA Appropriateness Method extrapolates from scientific-based evidence to assess whether clinical procedures at the level of patient-based characteristics (indications) are (1) inappropriate; (2) uncertain; or (3) appropriate. The authors extended the method to assess the basis for judgment by asking for each indication whether appropriateness was based upon (A): strong direct evidence, (B) weaker or indirect evidence, (C) consensus methods, or (D) personal opinion. This double-rating can be cast into a priority matrix, a logical form for prioritizing RCTs. For the high and medium priorities, a rank-ordering of cells further prioritized the indications. This matrix was tested in a 12-member Dutch expert panel study of combination treatments for rheumatoid arthritis, using 17 treatment combinations for each of 16 patient indications (272 ratings), and yielded results regarded by the panelists as reasonable, valid, and not entirely predictable. The authors concluded that expanded application of the RAND/UCLA Appropriateness Method can be used to prioritize the need for further research to provide evidence for clinical practice.
"RAND Europe."
Includes bibliographical references (p. 86-96).
Also available on the internet via WWW in PDF format.
In Dutch; summary in English.
Keywords: Antirheumatic agents -- Netherlands; Chemotherapy, Combination; Rheumatoid arthritis -- Chemotherapy -- Netherlands